The botanical explorations in Colombia: A review of the written botanical heritage with analyses of Lamiaceae collections as studied case - Antonio Villamil-Montero, Daniel [UNESP]; Ming, Lin Chau [UNESP] (Univ Santiago Chile Casa, 2016)
A chronological review of botanical explorations in Colombian was made through the revision of notes and publications from early 1500's to late 1990's. Complementary, herbaria photographs of Lamiaceae collections from botanical explorations in Colombia, deposited in the New York Botanical Garden Herbarium were analyzed in order to have a clear idea about the researches that were involved with collections in Colombia during the last 150 years..
Keywords: New Granada; Historical Botany; Naturalist; Expeditions; Collectors; Labiatae